A Poisoned Gift: digital platforms that promote new models of shared economy in tourism - Almeida, Paula (2018)
This paper seeks to approach the legal and social implications of digital platforms promoting new models of collaborative economy, focusing on those with low cost to the visitor, exchanging lodging and food for work hours dedicated to the host. We proceed with an analysis of the diploma that regulates volunteering, trying to understand the way in which the type of work performed by these tourists fits into the legal constraints of the concept, as well as what kinds of work relationships underlie the context of work exchange platforms. Likewise, we look at the online perceptions of these platforms, attempting to understand what might an individual find in searching for them, and what kinds of promises are made viz the reviews and descriptions of visits. We will in that sense attempt to open several lines of inquiry into these forms of touristic and professional relationships: can these platforms such as Helpaway, Hopineo, Worldpackers, Diverbo, Workaway and Helpstay be understood as mere mediators, or do they function as temporary work companies? Does this judicial figure of "voluntary work" not bear potential risk in terms of the extremely low cost, few obligations (such as insurance), and no protection asides from user ratings? What motivates individuals to want to participate in these relationships? We conclude with some remarks on these questions, pointing to the need of more research and a need to evaluate regulatory costs viz dynamical evolution of a lack of regulation.